Effect of pre‐injury anticoagulant and antiplatelet agents on blood loss in elderly patients with severe trauma. Issue 2 (27th August 2015) - Ohmori, Takao; Kitamura, Taisuke; Onishi, Hirokazu; Ishihara, Junko; Nojima, Tsuyoshi; Yamamoto, Koutarou
Abstract : Aim: It has been widely reported that pre‐injury use of anticoagulant and antiplatelet agents can affect traumatic brain injury and the associated risk of mortality, however, the effect of these agents on non‐head injury site‐related blood loss remains unclear. Therefore, we investigated the effects of pre‐injury anticoagulant and antiplatelet agents on the transfusion amount and the need for massive transfusion in elderly patients with severe trauma. Methods: We retrospectively reviewed a cohort of elderly patients with severe trauma (age, ≥65 years; Injury Severity Score, ≥16) between September 2006 and March 2014. The selected patients were subsequently divided into patients who were: only taking warfarin, aspirin, or clopidogrel; taking various combinations of these agents; and a control group who were not taking any of these agents. Results: During the study period, 67 patients (20%) were taking anticoagulant and antiplatelet agents and 272 patients were included in the control group. Among these patients, 10 were receiving only warfarin, 28 were receiving only aspirin, 14 were receiving only clopidogrel, and 13 were receiving various combinations of these medications. The amount of red cell concentrate and need for massive transfusions were only significantly increased in the warfarin group ( P < 0.05). Furthermore, the warfarin group had a significantly higher risk of needing a massive transfusion with multivariate logistic regression analysis (odds ratio, 5.03; 95% confidence interval, 1.25–20.20; P < 0.05). Conclusion: Patients who were receiving only warfarin before their injury had an increased risk of bleeding due to non‐head injuries.